The impact of digital literacy and technology adoption on financial inclusion in Africa, Asia, and Latin America - Nabil Adel (Heliyon)
Emerging countries face specific challenges in mobilizing the transformative potential of digital technology to achieve financial inclusion. While previous studies emphasize the role of digital infrastructure and technology adoption in financial inclusion, gaps remain in understanding how digital literacy and specific technologies, like blockchain, influence financial inclusion across diverse emerging regions. This study investigates the joint effect of digital literacy and blockchain adoption on financial inclusion in Africa, Asia, and Latin America from 2011 to 2021. Using a two-step system General Methods of Moments (GMM) model, we analyze data from 56 emerging countries to provide robust evidence on the impact of digital literacy and technology adoption on financial inclusion. Findings reveal that digital literacy enhances financial inclusion in Africa but unexpectedly hinders it in Asia, while new technology adoption consistently promotes inclusion in Asia and Latin America. Furthermore, internet penetration significantly boosts inclusion in Latin America, though it appears to reduce it in Asian contexts. Our results underscore the importance of region-specific digital strategies and highlight the need for targeted policy interventions to address regional disparities in financial inclusion.